Effects of conventional and organic rearing systems and hen age on oxidative stress parameters of blood and ovarian tissues in laying hens - Simsek, Ulku Gulcihan; Baykalir, Yasin; Erisir, Mine; Benzer, Fulya (Ankara Univ Press, 2018)
In this study, effects of hen age and rearing systems on some oxidative stress parameters in serum and ovarian tissues of hens are investigated. For this purpose, total of 48 Bovans White commercial laying hybrids from two different rearing systems (conventional cage and organic) at 30 and 60 weeks of age were used. Serum and ovarian tissues of the hens were collected following slaughter process and malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px) and catalase (CAT) levels of serum and ovarian tissues were determined. MDA levels of serum was found significantly higher in conventional system, both in 30 and 60 weeks old (P<0.05). GSH-Px activity was lower, conversely CAT activity was significantly higher in conventional system (P<0.05). Hen age didn't affect MDA, GSH, GSH-Px and CAT levels of serum (P>0.05). In addition, there weren't any significant interactions between rearing system and hen age in serum (P>0.05). MDA (P=0.010) and GSH (P<0.01) levels of ovarian tissue were found significantly higher in conventional system while GSH levels of ovarian tissue had increased in 60 weeks old (P<0.01). GSH-Px and CAT activity was similar between groups (P>0.05). Interaction between rearing system and hen age affected activity of CAT in ovarian tissue (P<0.05). As a result, conventional battery cages caused oxidative stress interrelated with increasing lipid peroxidation and MDA levels in laying hens. Antioxidant enzymes that play role in reduction of MDA were inadequate in this system. Oxidant/antioxidant balance can be established at 30 or 60 weeks of age by hen organism and therefore MDA levels of tissues would not be affected by age.
Konvansiyonel ve organik yetiştirme sistemleri ile tavuk yaşının yumurta tavuklarının kan ve yumurtalık dokusundaki oksidatif stres parametreleri üzerine etkisi
Keywords: Antioxidant activity; hen age; lipid peroxidation; rearing system